Report on the Beveridge proposals
1943-01-19 1943 1940s 20 pages 13. APPENDIX. 1. ADMINISTRATIVE. Should there be unification of administrative responsibility in the Ministry? The Committee are agreed as to the desirability of appointing a Minister who should be responsible for Social Insurance generally. Though we should favour one card for contributors, we doubt if it is administratively possible. This would not rule out the creation of separate Funds, which indeed may be considered desirable; and the Committee recommend that at any rate there should be a separate Unemployment Fund. Each town should have an office, with separate departments, to which all should have access. Independent local panels and appeal tribunals would be appointed. Such local bodies should be independent of control by local authorities. It is desirable that there should be a separate Fund for Unemployment which cannot be regarded as an insurable risk in the same sense as Health and Pensions risks. A distinction should continue to be drawn between short-term and long-term unemployment, and the Unemployment Fund should continue to make provision for statutory benefit for a fixed term and for an Assistance scheme depending on a means test. 2. COMPREHENSIVE INSURANCE. Should new classes be included in a compulsory scheme - for instance persons with private means who are well able to pay for the services of a private doctor and have no need of an old age pension? Should the State have to make a contribution from the taxpayers in respect of such persons? With regard to the Health and Rehabilitation Service, the majority of the Committee consider that compulsory insurance should be limited to persons up to a salary limit of £420 or possibly a 200/B/3/2/C216/5/93